Cultivating Resilience: A Key to Managing Academic Stress among Health Students in Online Learning - Abdillah, Hafizh Zain; Marleni (Psyche 165 Journal, 2023)
Academic stress refers to the pressure a person faces when dealing with academic demands. It is characterized by a variety of reactions, including physical, emotional, cognitive, and behavioral responses. The aim of this research is to empirically test the extent to which resilience contributes to academic stress among health students taking online learning at "X" University in the Bangka Belitung Islands during the New Normal period. The method used in this research is a quantitative approach with simple linear regression analysis. The sample for this study consisted of 143 health students at "X" University in the Bangka Belitung Islands, selected using cluster random sampling. Data was collected using a scale that measures the level of academic stress and the level of student resilience. The research results show that resilience plays a negative role in students' academic stress during online learning in the new normal period. The higher the level of resilience a student has, the lower their academic stress will be. Resilience accounts for 45.2% of the variance in academic stress, while the remaining 54.8% is influenced by other variables. These findings have important implications, showing that students need to enhance their resilience in order to reduce academic stress levels. In the context of online learning during the New Normal period, resilience can be a factor that helps students successfully cope with the academic pressure they face. Further research and holistic approaches to student well-being should also be considered to support increased resilience and reduced academic stress.